Esensialisme Dalam Pendidikan Islam - Muhammad Jawad Attaqy; Muhammad Fatih Hidayatullah; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2025)
Essentialism in educational philosophy emphasizes the importance of preserving cultural values and knowledge that have stood the test of time. This philosophical approach focuses on shaping individuals who can positively contribute to society through mastery of essential foundational knowledge. This article explores the core principles of essentialism, including cultural preservation, adaptation to natural laws, and the development of intelligence and character. In the educational context, essentialism stresses the need for a systematic and disciplined curriculum designed to encompass knowledge relevant to everyday life. Essentialist education also aims to shape students' character, enhance their intellectual capacities, and ensure that stable traditional values are upheld. Additionally, essentialism emerged as a critique of progressive education, which is seen as overly flexible and unstable. Essentialists argue that progressive education often neglects the importance of time-tested traditional values. By focusing on these values, essentialist education seeks to create stability and clarity within society. This article also discusses how essentialist education can be applied in modern contexts to achieve these goals and provides insights into the role of essentialism in maintaining social and cultural stability. Through this study, a deeper understanding of the relevance of essentialism in contemporary educational systems is expected